New species of ptyctimous mites (Acari, Oribatida) from Borneo and Sumatra - Niedbala, Wojciech (Zootaxa, 2008)
Twenty nine species of ptyctimous mites (Acari, Oribatida) were collected from Borneo, Sabah and Sarawak provinces (Malaysia) and Sumatra (Indonesia). Among them one species of Mesoplophoridae and six species of Phthiracaroidea, are described. They are: Mesoplophora (Parplophora) brevicarinata sp. nov., Plonaphacarus heterosetosus sp. nov., Plonaphacarus longicarinatus sp. nov., Hoplophthiracarus niahensis sp. nov., Hoplophthiracarus mielcareki sp. nov., Archiphthiracarus pachetos sp. nov. and Notophthiracarus abacus sp. nov. Half of the species found are endemics and nearly half of them are widespread.